George Washington Carver - Holt, Rackham (New York : Dell Publishing, 1967)
This special edition is for readers for whom english is a second language. It can be read by anyone who has learned 1,000 words of english.
A great american negro teacher.Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana